Scientific Dissemination in STEM Careers: The Case of the Costa Rican Institute of Technology - Castillo Vargas, Andrés (2025)
This article addresses the importance of scientific dissemination in STEM (Science, Technology, Engineering, and Mathematics) careers, highlighting its relevance in promoting a participatory dialogue between the scientific community and diverse audiences in society. From a quantitative approach, an online questionnaire was applied to a sample of researchers from the Costa Rican Institute of Technology, aiming to understand their attitudes and practices regarding the dissemination of technoscientific knowledge. The findings underscore the urgent need to strengthen academic regulations that encourage the undertaking of scientific dissemination activities. In conclusion, the scientific dissemination in STEM careers is a key mechanism for eliminating inequalities —both within and outside the academy— and for promoting active citizen participation in public decision-making based on evidence, addressing contemporary challenges in a collaborative and informed manner.